0
$\begingroup$

Suppose $f(-1 + i) = 2 + 5i$ and $f(-2 - i) = -3$ determine the remainder of $f(x)$ divided by $(x + 1 - i)(x + 2 + i)$.

I don't really know where to start any help would be great. Thanks :)

$\endgroup$
1

2 Answers 2

0
$\begingroup$

If $f(a)=s$ and $f(b)=t$, then by the polynomial division algorithm there are polynomials $q$ and $r$ such that $f(x)=(x-a)(x-b)q(x) + r(x)$ where $\deg r<2$.

This means $s=f(a)=r(a)$ and $t=f(b)=r(b)$, and since $r(x)=Ax+B$ for some constants $A$ and $B$, one can write by inspection that

$$r(x) =\frac{s\cdot(b-x)+t\cdot(x-a)}{b-a}.$$

Plug in your values $a=-1+i,b=-2-i,s=2+5i,t=-3$ and simplify.

$\endgroup$
0
$\begingroup$

Write $f(z) = h(z)*(z - z_1) + a$, and $f(z) = k(z)*(z - z_2) + b$, multiply the 1st equation by $z - z_2$, and the 2nd equation by $z - z_1$, and subtract the two new equations to get: $(z_1 - z_2)*f(z) = (h(z) - k(z))*(z - z_1)*(z - z_2) + a(z - z_1) - b(z - z_2)$, from this we can find the remainder.

$\endgroup$
2
  • $\begingroup$ To be honest I don't really understand what your answer means. Could you explain? $\endgroup$
    – olec
    Apr 2, 2014 at 4:10
  • $\begingroup$ @olec: this treats the general case. $\endgroup$
    – DeepSea
    Apr 2, 2014 at 7:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.